Glucose dysregulation in Parkinson's disease: Too much glucose or not enough insulin?. (October 2018) - Marques, Ana; Dutheil, Frédéric; Durand, Elodie; Rieu, Isabelle; Mulliez, Aurélien; Fantini, Maria Livia; Boirie, Yves; Durif, Franck
Abstract: Objective: To detect changes in glucose regulation in moderate to advanced Parkinson's disease (PD) patients in response to oral glucose intake. Methods: Blood glucose and insulin kinetics during a 75-g Oral Glucose Tolerance Test (OGTT) were compared between 50 PD patients and 50 healthy controls (CT) matched for body mass index (BMI), age and sex. Potential relationships between changes in glucose kinetics and clinical parameters were analyzed including Parkinson's disease severity and autonomic function using SCOPA-AUT (Scales for Outcomes in Parkinson's disease, Autonomic dysfunction). Results: Blood glucose was significantly higher at T90 ( p  = 0.04) and T150 ( p  = 0.01) in PD patients compared to healthy matched controls. Moreover, the total area under time curve (AUC) for the blood glucose levels was significantly higher in PD patients compared to healthy controls (1187 ± 229 vs 1101 ± 201 mmol min.l -1 ; p  = 0.05). Simultaneously, no significant increase of insulin levels was observed in PD patients compared to controls. Higher blood glucose levels were associated with higher BMI (p < 0.001), female gender (p < 0.033), longer duration of PD (p = 0.001), lower dose of dopaminergic treatment (p = 0.023), and higher score of dysautonomia (p = 0.017). Conclusion: Glucose control is impaired in moderate to advanced non-diabetic PD patients, due to impaired adaptive insulin response which may be a novel non-motor consequence of PD associated dysautonomia. Highlights: Blood glucose after oral glucose intake is higher in PD compared to healthy controls. Higher blood glucose is not associated with an expected rise in insulin levels in PD. Impaired adaptive insulin secretion in advanced PD could be due to dysautonomia.